Federated Aggregate Cohort Estimator (FACE): An easy to deploy, vendor neutral, multi-institutional cohort query architecture - Wyatt, Matthew C.; Hendrickson, R. Curtis; Ames, Michael; Bondy, Jessica; Ranauro, Paul; English, Thomas M.; Bobitt, Keith; Davidson, Arthur; Houston, Thomas K.; Embi, Peter J.; Berner, Eta S. (Journal of biomedical informatics, 2014)
•FACE is a federated, multi-platform approach for clinical study cohort estimation.•Data is aggregated from both i2b2 and Virtual Data Warehouse (VDW) data models.•The architecture helps meet IRB and security requirements easily with local control.•RESTful web services preserve security, logging, and features for i2b2 sources.•The virtual machine delivery model reduces the burden at each data sharing site. Cross-institutional data sharing for cohort discovery is critical to enabling future research. While particularly useful in rare diseases, the ability to target enrollment and to determine if an institution has a sufficient number of patients is valuable in all research, particularly in the initiation of projects and collaborations. An optimal technology solution would work with any source database with minimal resource investment for deployment and would meet all necessary security and confidentiality requirements of participating organizations. We describe a platform-neutral reference implementation to meet these requirements: the Federated Aggregate Cohort Estimator (FACE). FACE was developed and implemented through a collaboration of The University of Alabama at Birmingham (UAB), The Ohio State University (OSU), the University of Massachusetts Medical School (UMMS), and the Denver Health and Hospital Authority (DHHA) a clinical affiliate of the Colorado Clinical and Translational Sciences Institute. The reference implementation of FACE federated diverse SQL data sources and an i2b2 instance to estimate combined research subject availability from three institutions. It used easily-deployed virtual machines and addressed privacy and security concerns for data sharing.